1996
DOI: 10.1021/ac951169b
|View full text |Cite
|
Sign up to set email alerts
|

Polarimetry in Capillary Dimensions

Abstract: Microinterferometeric backscatter is employed to detect optically active molecules in capillary tubes. The capillary polarimetric detector (CPD) is based on the interaction between a polarized laser beam and a capillary tube. The simple optical configuration employs a He−Ne laser, a glass polarizing plate, a fused silica tube, and a CCD-based laser beam analyzer. Side illumination of the capillary produces a 360° fan of scattered light that contains two sets of high-contrast interference fringes. These light a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0
1

Year Published

1998
1998
2006
2006

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 17 publications
2
17
0
1
Order By: Relevance
“…In the case described here it is on the order of 40 nL. As shown previously [3] when orienting the plane of polarization of the incoming light coincident with the capillary central axes an additional set of high contrast fringes with a higher spatial frequency appears ( Fig. 3).…”
Section: Figuresupporting
confidence: 66%
See 2 more Smart Citations
“…In the case described here it is on the order of 40 nL. As shown previously [3] when orienting the plane of polarization of the incoming light coincident with the capillary central axes an additional set of high contrast fringes with a higher spatial frequency appears ( Fig. 3).…”
Section: Figuresupporting
confidence: 66%
“…2), or by introducing an optically active solute into the capillary. In this way, CPD can be used to quantify optically active solutes [2][3][4][5] or to determine optical rotary power of an unknown solute [5,6]. It is noteworthy that it has been previously shown that the polarimetry signal is contained within the high-frequency component of the CPD fringe pattern and the spatial frequency of this pattern does not change with concentration of nonoptically active solutes [2,5,6] (e.g., it is relatively insensitive to refractive index changes).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…25 A quantum leap in sensitivity has been achieved by Bornhop, who has described a microinterferometry method to obtain polarimetric information from picomolar amounts of chiral compounds held in a capillary tube of the type used for GC and HPLC analysis. 26,27 While an applicable device based on this technology has not yet been invented, the fundamental method holds great promise for bringing the direct measurement of optical purity to the necessary levels of scale, speed, and generality so as to be useful in high-throughput screening.…”
Section: Direct Detection Of Enantiomersmentioning
confidence: 99%
“…1 This has lead to the development of a series of alternative approaches to enantiomeric screening which span most areas of analytical chemistry. 2 However, polarimetry has far from been abandoned and recent demonstrations of gas phase cavity ring-down polarimetry, 3,4 frequency domain polarimetry, 5 and measurements of nanoliter volumes using capillary interferometry 6 illustrate the continued appeal of the technique largely due to its conceptual simplicity and its applicability to all chiral molecules.…”
mentioning
confidence: 99%